Long-term influence of mandibular advancement on the volume of the posterior airway in skeletal Class II-patients: a retrospective analysis. Issue 8 (October 2017) - Dalla Torre, D.; Burtscher, D.; Widmann, G.; Rasse, M.; Puelacher, T.; Puelacher, W.
Abstract: In the past, maxillomandibular advancement has resulted in considerable improvement in the volume of the posterior airway space. The objective of the present study was to find out how mandibular advancement without maxillary involvement would affect the posterior airway space in patients with mandibular retrognathism. Cone-beam computed tomographic (CT) scans were done for 20 patients before, and six months after, mandibular advancement. Cephalometric analysis at both time points included 2-dimensional and 3-dimensional assessment of the upper airway. Eight men and 12 women presented a preoperative mean (SD) Wits value of 7.4 (1.54) mm, with an airway area of 7.11 (1.88) cm 2 and a volume of 14.92 (4.46) cm 3 . Six months postoperatively they showed a Wits value of 2.7 (0.41) mm, an airway area of 11.33 (3.49) cm 2, and a volume of 25.7 (6.10) cm 3 . There was a mean (range) enlargement of 59 (22-82) % of the area and 73 (29-108) % of the volume. A preoperative Wits value of 8 mm or more correlated significantly with a larger increase of the posterior airway space (p = 0.002). At the same time, an improvement in the Wits value of 4.5 mm or more correlated significantly with an increase in volume (p = 0.016). The effect of mandibular advancement on the posterior airway space was significant, and the volumetric effect seems to be even more relevant than the two-dimensional changes.